Analysis of risk factors for benign central airway stenosis after COVID-19 infection - Ruiyang Wang; Jiuling Cheng; Yuping Zhang; Huaqi Wang (European Journal of Medical Research)
Abstract Background To investigate the risk factors associated with benign central airway stenosis following COVID-19 infection. Methods The clinical data of 235 patients hospitalized for COVID-19 infection at the First Affiliated Hospital of Zhengzhou University from October 2022 to October 2023 were retrospectively analyzed. Based on the occurrence of postoperative central airway stenosis, the patients were categorized into a stenosis group (118 cases) and a control group (117 cases). The incidence of central airway stenosis following COVID-19 infection was summarized. Univariate and multivariate logistic regression analyses were conducted to identify risk factors associated with central airway stenosis after COVID-19 infection. Results Among the 235 patients studied, 118 developed central airway stenosis. The results of the univariate analysis indicated that age, sex, liver function (as measured by alanine aminotransferase and aspartate aminotransferase values), renal function (creatinine values), diabetes mellitus, fungal airway infections, tuberculosis, and nutritional status (albumin values) were identified as risk factors for benign central airway stenosis following COVID-19 infection (P < 0.05). Furthermore, the multivariate analysis revealed that sex, diabetes mellitus, fungal airway infections, tuberculosis, and nutritional status (albumin values) were independent risk factors for benign central airway stenosis after COVID-19 infection (all P < 0.05). Conclusion diabetes mellitus, fungal airway infections, tuberculosis, and poor nutritional status may lead to benign central airway stenosis after COVID-19 infection. Proactive preventive measures and close monitoring should be taken to improve the quality of life of patients infected with COVID-19.